Analisis Kesalahan Fonologi dalam Maharah Qira’ah Siswa Madrasah Ibtidaiyah - Mahbubah, Latifatul; Ilmiyah, Taftinatul (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2024)
Language errors continue to be interesting research material to develop, especially language errors in foreign or second languages. This research aims to analyze errors in the pronunciation of the sound of the hijaiyah letters in the process of learning to read Arabic texts so that the results of this analysis can be an improvement for Arabic language teachers. This research uses descriptive qualitative research methods using several data analysis processes, namely data presentation, data reduction, data verification and drawing conclusions. The results of the research show that phonological errors in reading Arabic texts by class VI students at MI Nurus Salam Pamekasan have several forms, namely changing the sound of certain letters into the sound of other letters which are almost similar in articulation, omitting the sound of certain letters and/or omitting certain sound signs.